Costs of hospitalization in preterm infants: impact of antenatal steroid therapy - Joice Fabiola Meneguel Ogata; Marcelo Cunio Machado Fonseca; Milton Harumi Miyoshi; Maria Fernanda Branco de Almeida; Ruth Guinsburg (Brazilian Society of Pediatrics, 2016)
Objective: To estimate the costs of hospitalization in premature infants exposed or not to antenatal corticosteroids (ACS). Method: Retrospective cohort analysis of premature infants with gestational age of 26 to 32 weeks without congenital malformations, born between January of 2006 and December of 2009 in a tertiary, public university hospital. Maternal and neonatal demographic data, neonatal morbidities, and hospital inpatient services during the hospitalization were collected. The costs were analyzed using the microcosting technique. Results: Of 220 patients that met the inclusion criteria, 211 (96%) charts were reviewed: 170 newborns received at least one dose of antenatal corticosteroid and 41 did not receive the antenatal medication. There was a 14% to 37% reduction of the different cost components in infants exposed to ACS when the entire population was analyzed, without statistical significance. Regarding premature infants who were discharged alive, there was a 24% to 47% reduction of the components of the hospital services costs for the ACS group, with a significant decrease in the length of stay in the neonatal intensive care unit (NICU). In very‐low birth weight infants, considering only the survivors, ACS promoted a 30% to 50% reduction of all elements of the costs, with a 36% decrease in the total cost (p = 0.008). The survivors with gestational age < 30 weeks showed a decrease in the total cost of 38% (p = 0.008) and a 49% reduction of NICU length of stay (p = 0.011). Conclusion: ACS reduces the costs of hospitalization of premature infants who are discharged alive, especially those with very low birth weight and < 30 weeks of gestational age.